Species richness and diversity of aquatic insects inhabiting rice fields in Bogor, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wakhid, Rauf A, Krisanti M, Sumertajaya IM, Maryana N. 2020. Species richness and diversity of aquatic insects inhabiting rice fields in Bogor, West Java, Indonesia. Biodiversitas 21: 34-42. Rice fields occupy the largest cultivated area in agricultural landscape in Indonesia and support a variety of living organisms, including aquatic insects. This study was conducted with the objective to determine the species richness and diversity of aquatic insects inhabiting rice fields. Sampling was made in March, May, and July 2017 in rice fields at Situgede, Pandansari, and Kawungluwuk (Bogor region, West Java, Indonesia), and carried out by dragging dip net on the bottom along the edge of the rice plots. A total of 3,306 individuals representing 45 species of aquatic insects belonging to 30 genera, 20 families, and seven orders were recorded. Order Hemiptera was the most abundance comprising 28.89% of the total insects collected, followed by Diptera (24.80%), Coleoptera (24.41%), and Odonata (21.42%). Functional feeding group analysis showed that collectors-gatherers had the highest proportion (40 - 46%), followed by predators (23-44%) and scrapers (10-35%). Rank-abundance curve showed low species evenness with the four most abundant species were Micronecta siva (Kirkaldy) (Hemiptera: Micronectidae), Chironomus sp. (Diptera: Chironomidae), Orthetrum sabina (Drury) (Odonata: Libellulidae), and Helochares sp. (Coleoptera: Hydrophilidae). The Shannon-Wiener index showed the lowest value (H’=1.84) at Situgede and the highest (H’=2.05) at Pandansari. Richness estimate and individual-based rarefaction curve revealed that rice fields at Pandansari have more species richness than the other two sites. This study provides some insights into the aquatic insect community of the human-made ecosystem and suggests that the ecological approach to pest management is necessary for maintaining ecosystem health and promoting biodiversity.
Keywords: Aquatic insects, biodiversity, Bogor, rice fields